Analysis Of Musculoskeletal Complaints Among Packing Workers In The Frozen Food Industry: Japanese Taiyaki Cakes - Aura Wijayanti Kusuma; Muhammad Sabri Syahrir; Stefiani Bengan laba; Muhammad Aji Satria (Eduvest - Journal of Universal Studies, 2026)
Background:Musculoskeletal disorders (MSDs) are common occupational health problems caused by non-ergonomic postures and repetitive activities. Every year, more than 2.3 million workers die due to occupational accidents and diseases, including musculoskeletal complaints. Such conditions were also observed in a frozen Japanese Taiyaki cake industry in Indonesia, particularly among packing workers who stand for long periods and perform repetitive movements such as lifting, bending, and arranging products into packages. These activities are suspected to increase the risk of MSDs. This study aimed to analyze the prevalence of musculoskeletal complaints among packing workers in the frozen food industry. Method: A cross-sectional design was applied, involving 75 workers selected through purposive sampling. Data were collected using a validated Nordic Body Map (NBM) questionnaire along with respondent characteristics. Bivariate analysis was performed using the Chi-square test. Result: The results showed a prevalence of musculoskeletal complaints of 62.7%, with the most affected body parts being the lower back (40%), shoulders (26.7%), and neck (20%). The Chi-square analysis revealed that working duration of ≥ 8 hours per day (p = 0.001) and work period > 5 years (p = 0.003) were significantly associated with MSDs, while age and gender showed no significant relationship. Conclusion: In conclusion, the prevalence of MSDs among packing workers in the frozen food industry was relatively high, with work duration and length of employment as the main contributing factors. Ergonomic interventions such as work schedule adjustment, task rotation, and active stretching programs are recommended to reduce musculoskeletal complaints.